Global history, world history and globalization - Nataliya Gorodnia (Європейські історичні студії, 2019)
This paper is intended to describe and discuss the major concepts of global history, and to elucidate connections between global history, world history, and globalization. The research reveals that global history is a field of study and a methodology of historical research. These two concepts supplement each other. As a field of study global history is understood in two ways – a form of world history, based on some methodological principles, and a history of globalization. Global history appeared in 1980-1990s as a reaction on globalization, and it was influenced by its different concepts. Debates on globalization impacted world history, its themes and methods of research. Those world historians, who accepted the «global turn», began to practice global history. For the reason, the terms «global history» and «(new) world history» may be used as synonyms. A part of historians understand global history as a history of globalization. However, this definition is disputable because of numerous concepts of globalization and the absence of consensus on the issues. As a methodology global history consolidates different approaches, such as world systems theory, postcolonial history, transnational history, subaltern history, imperial history, and others. They share similar principles that include a rejection of Eurocentrism, an understanding of the past as an integrated unit, interdisciplinary approach, and a focus on connections, interactions and mutual influences that transcend borders (national, cultural, and others). Global history prefers some specific research topics that are trans-national and trans-cultural in nature, because in these cases it has the strongest explanatory power. However, as a methodology it can be applied to different scales of human experience, including events and processes at local, national, and regional levels by studying them from a wider, global perspective.